The relationship between external factors and economic growth: Differences between the global financial crisis and the COVID-19 pandemic from a Granger causality perspective - Alexandra CHEPTIS; Cristina BEJENARU; Miruna-Mihaela VASILCA; Alin-Ioan VID (Theoretical and Applied Economics)

(untitled)
The paper investigates the causal relationship between external factors and economic growth in three countries from Central and Eastern Europe and contains a series of complex analyses on the study of typologies of economic crises. The study includes Markov-Switching Autoregressive (MS-AR) models for characterizing business cycles, and the Granger causality technique is used to analyze the relationship between external shocks and economic growth, separately during financial and pandemic crises. The results indicated that, in the case of Romania, the global financial crisis has a longer period of negative growth rates, but a faster recovery from health crisis. It is also noted that the Czech Republic and Hungary have a more stable economic evolution over time. In addition, the causality test indicates unidirectional causality between external factors and the GDP growth rate during financial and pandemic crises.